THE ROLE OF PERCEIVED VALUE IN MEDIATING THE EFFECT OF ATTITUDE TOWARD AR VTO ON REUSE INTENTION(A Study on Cosmetic AR VTO Users in Denpasar City) - Jassincha Khansa Duandri; Ni Made Asti Aksari (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
The development of augmented reality virtual try-on (AR VTO) technology in the digital cosmetics industry presents both opportunities and challenges in encouraging the sustainable use of this technology by consumers. This study aims to examine the effect of attitude toward AR VTO on reuse intention, the effect of attitude toward AR VTO on perceived value, the effect of perceived value on reuse intention, and the mediating role of perceived value in the relationship between attitude toward AR VTO and reuse intention among cosmetic AR VTO users in Denpasar City. This research is grounded in the Theory of Reasoned Action (TRA) and employs a quantitative approach with data collection conducted through questionnaires distributed to 120 Generation Z respondents in Denpasar City who had previously used cosmetic AR VTO features. The data analysis method used was Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The findings indicate that attitude toward AR VTO has a positive and significant effect on reuse intention, attitude toward AR VTO has a positive and significant effect on perceived value, perceived value has a positive and significant effect on reuse intention, and perceived value partially mediates the relationship between attitude toward AR VTO and reuse intention. These findings extend the causal chain of the Theory of Reasoned Action into a belief–attitude–perceived value–intention framework, with rational indicators in attitude and functional value indicators in perceived value emerging as the dominant factors driving the reuse intention of cosmetic AR VTO in Denpasar City.